Substantial utilization of Facebook, Twitter, YouTube, and Instagram in the prostate cancer community - Struck, Julian; Siegel, Fabian (World journal of urology, 2018)
PurposeTo measure the usage rate of social media (SoMe) resources in the prostate cancer community, we performed a comprehensive quantitative and qualitative assessment of SoMe activity on the topic of PCa on the four most frequented platforms.MethodsWe scanned the SoMe platforms Facebook, Twitter, YouTube, and Instagram for “prostate cancer” as a cross-sectional analysis or during a defined time period. Sources were included if their communication centered on PCa by title and content. We assessed activity measurements for each SoMe source and classified the sources into six functional categories.ResultsWe identified 99 PCa-related Facebook groups that amassed 31,262 members and 90 Facebook pages with 283,996 “likes”. On YouTube, we found 536 PCa videos accounting for 43,966,634 views, 52,655 likes, 8597 dislikes, and 12,393 comments. During a 1-year time period, 32,537 users generated 110,971 tweets on #ProstateCancer on Twitter, providing over 544 million impressions. During a 1-month time period, 638 contributors posted 1081 posts on Instagram, generating over 22,000 likes and 4,748,159 impressions. Among six functional categories, general information/support dominated the SoMe landscape on all SoMe platforms.ConclusionSoMe activity on the topic of PCa on the four most frequented platforms is high. Facebook groups, YouTube videos, and Twitter tweets are mainly used for giving general information on PCa and education. High SoMe utilization in the PCa community underlines its future role for communication of PCa.
Gesehen am 18.04.2019